Jane Eyre's Rooks and Crows. (2nd January 2021) - O'Gorman, Francis
Abstract : This short paper looks again at an intriguing pattern in Charlotte Brontë's imagining of corvids in Jane Eyre (1847), suggesting that these creatures are indications of a particular, and very probably unconscious, imaginative habit in the novel. The birds appear in the text at crucial moments as if they are closely associated in Charlotte's mind with important turns in the plot. The end of the paper considers the subtle implications of these creatures of the air for the novel's wider interest in the air itself.